Measurement of the production cross-section of J/ψ and ψ (2S) mesons in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (The European physical journal. C, Particles and fields, 2024)
Measurements of the differential production cross-sections of prompt and non-prompt J/psi and psi(2S) mesons with transverse momenta between 8 and 360 GeV and rapidity in the range vertical bar y vertical bar < 2 are reported. Furthermore, measurements of the non-prompt fractions of J/psi and psi(2S), and the prompt and non-prompt psi(2S)-to-J/psi production ratios, are presented. The analysis is performed using 140 fb(-1) of root s = 13 TeV pp collision data recorded by the ATLAS detector at the LHC during the years 2015-2018.
ATLAS Collaboration: G. Aad, F. Bartels, F.L. Castillo, M Czurylo, F. del Rio, S. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und 2924 weitere
Online veröffentlicht: 19. Februar 2024
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 20.11.2024